2021
DOI: 10.1007/s11263-021-01485-5
|View full text |Cite
|
Sign up to set email alerts
|

Learned Collaborative Stereo Refinement

Abstract: In this work, we propose a learning-based method to denoise and refine disparity maps. The proposed variational network arises naturally from unrolling the iterates of a proximal gradient method applied to a variational energy defined in a joint disparity, color, and confidence image space. Our method allows to learn a robust collaborative regularizer leveraging the joint statistics of the color image, the confidence map and the disparity map. Due to the variational structure of our method, the individual step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…As the error threshold increased to 3 and 5, the reduction in mismatch rate became more significant, indicating an overall decrease in mismatch rate. (6) The qualitative comparison results on the KITTI2012 test dataset, using disparity prediction as the evaluation metric, are presented in Figure 11.…”
Section: Comparative Experimental Analysis On Three Major Public Data...mentioning
confidence: 99%
See 2 more Smart Citations
“…As the error threshold increased to 3 and 5, the reduction in mismatch rate became more significant, indicating an overall decrease in mismatch rate. (6) The qualitative comparison results on the KITTI2012 test dataset, using disparity prediction as the evaluation metric, are presented in Figure 11.…”
Section: Comparative Experimental Analysis On Three Major Public Data...mentioning
confidence: 99%
“…As the error threshold increased to 3 and 5, the reduction in mismatch rate became more significant, indicating an overall decrease in mismatch rate. (6) The qualitative comparison results on the KITTI2012 test dataset, using disparity prediction as the evaluation metric, are presented in Figure 11. From the figure, it can be observed that, compared to the PSMNet algorithm, the MANet algorithm predicted more continuous disparities in areas such as the sky and trees.…”
Section: Comparative Experimental Analysis On Three Major Public Data...mentioning
confidence: 99%
See 1 more Smart Citation